Environmental Reporting Practices in an Emerging Economy - S. M. Faridul Islam; Syed Zabid Hossain (Indonesian Journal of Sustainability Accounting and Management, 2022)
The study aimed to recognize the environmental awareness of corporate entities by exploring the extent of their associated information reporting practices. The study also strived to learn the notable board characteristics that transform the environmental reporting practices of the listed companies in an emerging market economy. This quantitative study was based on annual reports of randomly selected 100 manufacturing companies listed on the Dhaka Stock Exchange. The research used a self-developed disclosure index linked to the environment to collect data for the study. The study revealed that the extent of average environmental reporting practices by the sampled companies was too low, which was only 14.48% of the disclosure index developed for this study. Moreover, 4% of the selected companies did not disclose any environmental information in their annual report for the fiscal year 2018–2019. The most disclosed theme was the concern for the general environment, whereas the lowest was the environmental performance, which was between 25.83% and 6.2%. The study documented that no other board characteristics were highly significant and could positively explain the extent of corporate environmental reporting practices in Bangladesh, only the willingness to disclose by the board.